Ideology in Management Studies. (13th August 2019) - Seeck, Hannele; Sturdy, Andrew; Boncori, Anne‐Laure; Fougère, Martin
Abstract: Ideology is a core and contested concept in the social sciences, but also long deployed in management research to highlight the political, embedded and/or obscuring nature of ideas. Indeed, many would argue that management itself is inherently ideological in legitimating or privileging managerial interests and concealing other groups and ways of organizing. In the first systematic review of how ideology has been conceptualized in management studies, this paper explores its diverse and changing meanings in order to develop and sustain the concept. It is based on a heuristic review of 175 articles and 41 books published between 1956 and 2018. Further developing categories used in the social sciences around its role, we found views of ideology as: (1) domination; (2) legitimation; (3) interpretation; (4) integration; and (5) normative logic. In addition, emerging perspectives were identified where ideology was (6) an object of critique or (7) fantasy structuring social reality. We describe, illustrate and evaluate these often internally diverse and interrelated perspectives, as well as comparing them with sometimes competing notions within the management field, such as discourse, culture and legitimation. We also bring together the different approaches and argue for a pluralist, but not infinitely flexible, approach to the concept. In doing so, we identify research agendas for ideology within management and organization studies.